Different hyaluronic acid morphology modulates primary articular chondrocyte behavior in hyaluronic acid-coated polycaprolactone scaffolds - Lebourg, Myriam (2013)
Scaffolds for cartilage tissue engineering should promote both adequate biomechanical environment and chondrogenic stimulation. Hyaluronic acid (HA) has been used in cartilage engineering for its chondrogenic and chondroprotective properties, nevertheless its mechanical properties are limited. Influence of HA microstructure in chondrocyte response has not been addressed yet. In this work, polycaprolactone (PCL) scaffolds were modified using HA following two coating strategies: coating in one step (PCL-HA1s) yields a gel-like phase within the scaffold, whereas a two-step reaction (PCL-HA2s) yields a thin HA layer coating internal surfaces of PCL structure. Chondrocytes were seeded in the scaffolds and cultured in dedifferentiating conditions up to 3 weeks and analyzed using a total DNA assay and sulfated glycosaminoglycan (sGAG) determination assay; cell morphology and extracellular matrix secretion were assessed by electron microscopy as well as immunofluorescent imaging (collagen I, collagen II, aggrecan, CD44). Cells proliferate in all samples and no cytotoxicity is observed. PCL-HA1s shows higher sGAG production per cell than PCL and PCL-HA2s at all times. Presence of hyaluronic acid promotes qualitative expression of CD44 surface markers and aggrecan (more visible in PCL-HA1s than PCL-HA2s), whereas in dedifferentiating conditions, expression of CD44 and aggrecan can hardly be detected in pure PCL scaffolds. Collagen type II seems more prominent in PCL-HA2s; although PCLHA2s shows markers for COL II, aggrecan and CD44, quantitative ECM production is not improved with respect to PCL. It is thus likely that CD44 activation is not sufficient for explaining the better response in PCL-HA1s.